Delivery of germacrone (GER) using macrophages-targeted polymeric nanoparticles and its application in rheumatoid arthritis. (31st December 2022) - Tan, Tingfei; Huang, Qi; Chu, Weiwei; Li, Bo; Wu, Jingjing; Xia, Quan; Cao, Xi
Abstract: Macrophages can transform into M1 (pro-inflammatory) and M2 (anti-inflammatory) phenotypes, which mediate the immune/inflammatory response in rheumatoid arthritis (RA). Activated M1 phenotype macrophages and overexpression of folate (FA) receptors are abundant in inflammatory synovium and joints and promote the progression of RA. Germacrone (GER) can regulate the T helper 1 cell (Th1)/the T helper 2 cell (Th2) balance to delay the progression of arthritis. To deliver GER to inflammatory tissue cells to reverse M1-type proinflammatory cells and reduce inflammation, FA receptor-targeting nanocarriers loaded with GER were developed. In activated macrophages, FA-NPs/DiD showed significantly higher uptake efficiency than NPs/DiD. In vitro experiments confirmed that FA-NPs/GER could promote the transformation of M1 macrophages into M2 macrophages. In adjuvant-induced arthritis (AIA) rats, the biodistribution profiles showed selective accumulation at the inflammatory site of FA-NPs/GER, and significantly reduced the swelling and inflammation infiltration of the rat's foot. The levels of pro-inflammatory cytokines (TNF-α, IL-1β) in the rat's inflammatory tissue were significantly lower than other treatment groups, which indicated a significant therapeutic effect in AIA rats. Taken together, macrophage-targeting nanocarriers loaded with GER are a safe and effective method for the treatment of RA.